Plan Estratégico de Marketing para la Empresa “Tilapias De Oriente” de la Provincia de Zamora Chinchipe, Parroquia Pachicutza, Periodo Abril-Agosto 2020.” - Uquillas Maldonado, José Eduardo (2021)
In this research, the environment of the company “Tilapias de Oriente” was analyzed, for this the PESTEC analysis was used, which is reflected in the external factors evaluation matrix, resulting in 2.96 obtaining more opportunities than threats. To measure competitiveness, the analysis of the five forces of Porter was used, which helped to establish the level of competitiveness, resulting in the MPC 2.90 being the company in a good position but that can be improved. For the internal analysis, the internal factors evaluation matrix was used, analyzing the strengths and weaknesses that the company has in each of the functional areas, obtaining a result of 2.82; being a good result but that can be improved. We proceeded to diagnose how the company is using the high impact SWOT matrix, the same one that combines the EFE and EFI matrix, obtaining strategies in the different quadrants. Likewise, the internal and external matrix was made, combining the results of the EFE and EFI matrices, resulting in quadrant V, so it is recommended to establish market penetration strategies. The Mckinsey matrix was used which analyzes the attractiveness of the market and competitiveness, resulting in 3.80 for competitiveness and 3.65 for the attractiveness of the industry. Finally, strategic objectives were raised and the marketing plan proposal for the company was carried out, which consists of activities, responsible personnel, schedule and budget.